Analisis Kepuasan Pengguna Sistem Rekam Medis Elektronik Menggunakan Metode EUCS di RS Hermina Kota Padang - Kamal, Syamsul; Mayasari, Nila; Khairani, Dila (Akademi Perekam dan Informasi Kesehatan Imelda, 2024)
There are 6 Pillars of Health Transformation, one of which is the 6th pillar, namely Health Technology Transformation, which has a role in utilizing information technology so that with health information technology we can make good use of developments in digital technology, so that the process of digitizing health technology can grow better and grow better. developing in the world of health. In Minister of Health Regulation Number 24 of 2022 concerning Electronic Medical Records, it is stipulated that all Health Facilities at the end of December 2023 must implement RME, where the change from Manual Medical Records to Electronic Medical Records (RME). The aim of this research is to look at user satisfaction regarding the content, appearance, data accuracy, timeliness and ease of Hinai application for RME at Hermina Hospital. The method used in this research is the Quantitative Method with a descriptive approach. In carrying out data processing, the EUCS method was used with 18 samples. This research was carried out in May 2024 at Hermina Hospital, Padang City. The results of the research showed that users were very satisfied with the performance of the Hinai application, where the content got a score of 79 and a TCR of 87.78% for the display, a score of 81 and a TCR of 90.89 were obtained, for data accuracy it was 79.2 and the TCR was 80%, for accuracy When we got a score of 80 and a TCR of 88.89%, then for convenience we got a result of 80.4 and a TCR of 89.32, where for all categories it can be said that users of the Hinai application are very satisfied with the presence of this application and can continue using it in the future. . It is recommended that there be a continuation of this research for further development regarding the Hinai Application program in the future.